2023
DOI: 10.1093/ecco-jcc/jjad124
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Effectiveness of Vedolizumab Versus Ustekinumab After Anti-TNF Failure in Crohn’s Disease (Versus-CD): Data from the ENEIDA Registry

Abstract: Background Both vedolizumab and ustekinumab are approved for the management of Crohn’s disease (CD). Data on which one would be the most beneficial option when anti-TNF agents fail are limited. Aims To compare the durability, effectiveness and safety of vedolizumab and ustekinumab after anti-TNF failure or intolerance in CD. Methods CD patients from ENEIDA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Nine studies reported clinical or steroid-free clinical remission after the induction doses of ustekinumab and vedolizumab (Table 2A) [8,[11][12][13][14][15][16]18,20]. Four studies reported that ustekinumab was superior in achieving clinical remission after induction therapy compared to vedolizumab [8,14,18,20], and the rest (five studies) did not show any statistical differences in outcome after induction therapy [10][11][12][13]15].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine studies reported clinical or steroid-free clinical remission after the induction doses of ustekinumab and vedolizumab (Table 2A) [8,[11][12][13][14][15][16]18,20]. Four studies reported that ustekinumab was superior in achieving clinical remission after induction therapy compared to vedolizumab [8,14,18,20], and the rest (five studies) did not show any statistical differences in outcome after induction therapy [10][11][12][13]15].…”
Section: Discussionmentioning
confidence: 99%
“…Among studies which reported clinical outcomes at the end of the first year (week 48-week 52) of treatment (Table 2B), eight studies showed a superior clinical response rate and or steroid-free clinical remission for ustekinumab compared to vedolizumab [7,8,11,12,14,17,18,20], four studies showed no difference in the clinical response rate or steroid-free clinical remission between both drugs [9,10,13,19], and only a single study showed that vedolizumab achieved a superior clinical response rate [16]. However, in that study by Onali et al, no differences were observed when objective markers of inflammation were considered [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations